“Cultura organizacional y su relación con el desempeño laboral del personal administrativo y operativo de la empresa AIRNET del cantón Quevedo, año 2023”. - Bravo Rivera, Priscila Elizabeth (2024)
This research focuses on the importance of organizational culture in the work performance of the company AIRNET. Organizational culture is a key element in a company's success, as it can influence how employees perform and how the company is perceived both internally and externally. It is important that companies understand and manage their organizational culture effectively to create a positive and productive work environment. The methodology applied in this research was mixed, qualitative and quantitative, adding descriptive and analytical field, through the use of Tools such as interviews, surveys and reliability ranges, such as Kendal's w test, and the Cronbach index, are presented in the survey according to the Likert scale. The results exposed a series of data with values of less than 50% of job satisfaction, indicating an organizational culture weakened by the lack of communication, support and satisfaction, 45.8% agree that communication is weak which entails other internal consequences for the staff. administrative and operational. For these reasons, it is recommended to create spaces where you can train, relate and contribute to the company, value the contributions of workers and empower them in the company to be able to meet the objectives set and be competitive in the internet service market.